Agronomic Characteristics and Forage Yield of Brown Midrib (BMR) Sorghum in The Ratoon System - Riesi Sriagtula; Qurrata Aini; Mardhiyetti; Yetmaneli; Gusri Yanti; Le Huu Phuoc (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Brown Midrib (BMR) sorghum is a mutation-derived variety with low lignin and high non-structural carbohydrate content, potential as a ruminant forage. The ratoon system allows for repeated harvesting without replanting, thus providing an efficient forage supply. This study aimed to evaluate the agronomic characteristics and biomass productivity of BMR mutant sorghum in primary plants, the first and second ratoon. The study was conducted experimentally using a randomized block design with three treatments (primary, first ratoon, and second ratoon plants) and four replications. The parameters observed included agronomic components (plant height, number of tillers, stem diameter, and leaf size), stem sugar value (Brix), proportion of plant structures (stems, leaves, and panicles), panicle production, forage production, and livestock carrying capacity. The results showed that plant height was not significantly different (P>0.05) between primary and ratoon plants, while stem diameter and leaf size decreased gradually from the first to the second ratoon. The Brix value showed a highly significant difference (P<0.01), with the highest value in the first ratoon and the lowest in the second ratoon. The proportion of stems and leaves decreased in the second ratoon, whereas the proportion of panicles and panicle production increased significantly (P<0.01). The highest forage production was obtained in the second ratoon at 52.08 tons/ha, while the total production of the three harvests reached 112.28 tons/ha with a carrying capacity of 8.8 AU/ha. From the results of this study, it can be concluded that the ratoon system does not reduce the biomass productivity of BMR mutant sorghum and can maintain agronomic quality until the second ratoon. With its high production potential and good regrowth ability, BMR mutant sorghum is worthy of development as a sustainable forage source in ruminant livestock farming systems.